Analysis of Separation of Hydrogen and Oxygen Gases from Water through Water Electrolysis Experiments - Reinhard P Sihotang; Elsama Christina Manalu; Ryandi Simbolon (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Electrolysis of water is the decomposition of water compounds (H2O) into oxygen (O2) and hydrogen gas (H2) using an electric current that passes through the water. At the cathode, two water molecules react by capturing two electrons, reducing them to H2 gas and a hydroxide ion (OH-). Meanwhile at the anode, two other water molecules decompose into oxygen gas (O2), release 4H+ ions and flow electrons to the cathode. The H+ and OH- ions undergo neutralization so that some water molecules are formed again. The hydrogen and oxygen gases generated from this reaction form bubbles at the electrodes and can be collected. This principle is then utilized to produce hydrogen and hydrogen peroxide (H2O2) which can be used as fuel for hydrogen vehicles.